Legal immunity and liability in emergency assistance: Rethinking the Good Samaritan Doctrine in Indonesia through comparative and international perspectives - Faizal Kurniawan; Xavier Nugraha; Angelica Milano; Bryan Owen Soeprapto; Lorenzo Nieuwenburg (Jurnal Hukum Novelty, 2026)
Introduction to the Problem: The problem explored in this study is that the Indonesian legal system does not provide any legal protection for ‘Good Samaritan’ acting to aid others’ in grave danger. This legal vacuum might cause a shift in humans' good nature. Purpose/Study Objectives: The purpose of this study is to examine how other jurisdictions regulate Good Samaritan immunity in civil disputes, addressing the research gap in Indonesia where no protection exists, and how such frameworks may be adapted. Design/Methodology/Approach: Normative juridical research combining statute, conceptual, comparative, and case approaches across Indonesia, Canada, and China to map immunity/liability rules in emergency civil disputes and extract transferable principles relevant to international law debates on protecting life and enabling bystander aid. Findings: The study finds that implementing a Good Samaritan Doctrine in Indonesia addresses the current legal vacuum by providing immunity to individuals who render aid in emergencies. Comparatively, Canada grants civil immunity for Good Samaritans acting in good faith, while China’s Civil Code provides similar protection with limitations. These models demonstrate that clear immunity provisions can encourage voluntary assistance without exposing helpers to liability. In the Indonesian context, the idea of having legal immunity and liability for ‘Good Samaritans’ could be achieved in the short term through advocation clarifying judicial interpretation of Article 1354 of the Indonesian Civil Code, and in the long term through dedicated legislation establishing Good Samaritan protection.  Paper Type: Research Article